Short Communication: Occurrence and cluster analysis of palm oil (Elaeis guineensis) fruit type using two-dimensional thin layer chromatography - DENI ARIFIYANTO; MOHAMMAD BASYUNI; SUMARDI SUMARDI; LOLLIE AGUSTINA PANCAWARASWATI PUTRI; ETTI SARTINA SIREGAR; IWAN RISNASARI; INDRA SYAHPUTRA (Society for Indonesian Biodiversity, 2017)
Arifiyanto D, Basyuni M, Sumardi, Putri LAP, Siregar ES, Risnasari I, Syahputra I. 2017. Short Communication: Occurrence and cluster analysis of palm oil (Elaeis guineensis) fruit type using two-dimensional thin layer chromatography. Biodiversitas 18: 1487- 1492. The problems that have been faced by palm oil breeders are the length of time and high costs to discover the type of palm oil (Elaeis guineensis) fruit namely Dura, Pisifera, or Tenera, before using as a seed parent. These conditions are ineffective and add to the cost of maintenance and the production of seedling is more expensive. The present study describes the occurrence and cluster analysis of palm oil fruits using two-dimensional thin layer chromatography (2D-TLC). The leaves and fruit on each fruit mesocarp and shell, commercial seed on each fruit type were sampled through direct determination, plant nurseries, commercial seed and unknown type of palm oil. 2D-TLC chromatograms of hexane extracts showed diversity in palm oil fruits: Dura had ficaprenol-type polyprenol (C50-C60) and no carbon chain-length of polyprenol and dolichols (C85-C100) were found. In Tenera polyprenols of C45-C60 and C90-C100 occurred and dolichols of C85-C105 as well, where polyprenols of C45 and C105 and dolichol of C105 found in Tenera were not detected in Pisifera. To confirm these findings, cluster analysis was drawn using the UPGMA method. The dendrogram demonstrated that the three types of palm oil were grouped to fruit type, suggesting that the occurrence of polyisoprenoids in palm oil fruits were chemotaxonomically significant.